Pemanfaatan Teknologi Informasi dalam Integrasi Pendidikan Agama untuk Meningkatkan Hasil Belajar Siswa SMA Muhammadiyah MBS Weleri Kendal - Adiyah Mahiruna; Alfin Muslikhun; Safaat Yulianto; Mukhlidin Mukhlidin; Meia Rizqi Talita Putri; Annisa Reni Rahmawati; Nimas Ayu Puji Astuti (Karawo : Journal of Community Service (KJCS), 2025)
Information technology in the near future is indeed experiencing a very drastic change towards progress so that it needs to be utilized properly. By utilizing information technology combined with religious education, it will have a positive impact in improving academic and non-academic achievements. There are still many people who have difficulty in managing time so that more time is used towards information technology than towards religious education. By harmonizing the two in balance, humans will become lucky creatures. The purpose of this community service activity is to provide training to students of SMA Muhammadiyah MBS Weleri to be able to utilize information technology combined with Islamic religious education taught at school to achieve good achievements. Participants in this service are XII grade students at SMA Muhammadiyah MBS Weleri who will later face school graduation exams. So the need for time management so that they can divide their time well. The results of this community service are able to provide scientific knowledge in utilizing cellphones properly and wisely for reminders of both religious and learning activities.